Inovasi Pelayanan Publik Program E-Retribusi Di Dinas Perdagangan Kota Surakarta - Lies Fajarwati Wijaya; Winarti Winarti; Joko Suranto (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2020)
The e-retribution public service innovation by the Surakarta City Trade Office is a new concept regarding the online levy payment system. First launched in mid-2016, E-retribution as part of the implementation of smart government is included in the smart city indicator. This study uses the typology theory of public service innovation Muluk (2008). Research location in the city trade office Surakarta, with a qualitative descriptive method. The data collection technique was obtained by purposive sampling through informant interviews, observations and documents. The results show that the public service innovation with the e-retribution program can simplifying public services and saving more time, costs and human resources, ensuring accountable transactions. In addition, E-retribution has an impact on increasing Solo Local Revenue every year.